SYSTEM APPROACH IN FORMATION FACTORS’ INFLUENCE ON THE IMPLEMENTATION OF TRANSPORT SERVICES - Shamil Shavketovich Iksanov (Современная наука и инновации, 2022)
In this article the author suggests the definition of the main entities participating in the process of intercity transportation of cargo or having a direct impact on them. By the result of the description of the key entities for each of them, the factors influencing them have been revealed. Factors are characterized by a set of indicators that are presented in a formalized form with the transfer of data and vehicles using a mathematical apparatus.